TEMPORAL VARIATION OF CODA-Q AT GALERAS VOLCANO, COLOMBIA - Moncayo, Édgar; Vargas, Carlos; Durán, Juan (Earth Sciences Research Journal, 2004)
The Temporal variation of coda-Q was analyzed for Galeras volcano, located in the Andes of southwestern Colombia. The Q -1 value was calculated using the Single Back Scattering (SBS) model working with seismograms filtered in frequency bands centered in 1.5, 3.0, 6.0 and 12.0 Hz. The analysis was done in 1990-2002 period, using the URCR station and the frequency dependence Q = Qo f -n was calculated before and after some eruptions. We used volcano tectonic events with magnitude lower than 1.5 and RMS, GAP, vertical and horizontal errors lower than 0.1s, 180 and 1km.The temporal change of attenuation occurred in two stages, the first in 1989-1992 period, when the Q -1 value increases from 0.015 to 0.070. The second is the 1992-2002 period that is characterized by a decreasing Q -1 value. Before July 1992 eruption the attenuation increase is associated with the extrusion of an andesitic dome, after this eruption the dome was destroyed and the Q -1 value drops. Starting from 1994 low attenuation values was associated with low Galera's activity. The analysis shows that Q value increases before an eruption and decreases after it.